Analisis Keefektivitasan Program Ngaji Sore Dalam Meningkatkan Kualitas Bacaan Anak Di Desa Baru - Zainab, Siregar; Tanjung, Ellisa Fitri (Journal of Community Sustainability, 2024)
The afternoon Qur'an recitation program is one of the efforts implemented in Desa Baru to improve children's ability to read the Qur'an. This study aims to analyze the effectiveness of the program in enhancing the quality of children's Qur'an recitation, covering aspects such as tajwid (rules of Qur'anic pronunciation), fluency in reading, and memorization of short verses. This study employs a qualitative descriptive method, with data collection techniques including observation, in-depth interviews with instructors, child participants, and parents, as well as documentation of the children's reading progress. The research subjects include 20 child participants of the afternoon Qur'an recitation program, 3 instructors, and 10 parents. The results indicate that the afternoon Qur'an recitation program plays a significant role in improving children's reading abilities. The success of the program is influenced by several factors, such as varied teaching methods, the close relationship between instructors and participants, and active support from parents. However, challenges remain, including limited study time and a lack of interest in learning among some children. This study concludes that the afternoon Qur'an recitation program is effective in improving the quality of Qur'an recitation among children in Desa Baru, and it is hoped that this program can serve as a learning model to be applied in other villages with modifications according to local conditions.